KONSEP, SISTEM DAN STRUKTUR KBK SEBAGAI LANDASAN PENGEMBANGAN KURIKULUMDALAM UPAYA PENINGKATAN KUALITASLULUSAN PROGRAM STUDI PJKR FIKUNIVERSITAS NEGERI YOGYAKARTA - Djoko Pekik Irianto (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2006)
Curriculum is one of the importance components other then human resources andinfrastructure in the effort on providing high quality graduate. Update on the curriculumcontinuously is necessary to follow the demand of market and stakeholders which changeaccording to the current situation of society and global development. Learning tools forPJKR FIK UNY students use the PJKR 2002 curriculum need to be evaluated and updatedwith the society demand and development of education vision to implement competencebased curriculum. Several aspects to be brought in attention among others is adaptationwith overall juridical based: UU no.20, 2003 on national education system, SK MendiknasNo. 232/U/2000 on curriculum development and learning measurement, SK Mendiknas no045/U/2002 on core curriculum of high education, and PP No.19 2005 on national educationstandard. Strategic actions to be brought is: (a) reconstruction of vision, mission and goalsof physical education programme study, (b) re-formulate pure science subject to relevantrelated subject with competence demand, (c) explore relevance competence with societyand stakeholders need, (d) adapt common ground curriculum pattern with actual competencedemand, (e) to reduce and if necessary erase uniformity of curriculum.Keywords: competence based curriculum, PJKR, re-formulate, uniformity.